[Spanish translation] Where the game begins: home court advantage and performance contexts in female youth basketball leagues - López-García, Adrián (2026)
PURPOSE: The purpose of this study was to research on the extent of home court advantage (HA) and the percentage of home wins (HW), and to compare both metrics between different age categories (U14, U16 and U18) and the levels of ability in female youth basketball teams. METHODOLOGY: Data were gathered from the Madrid Basketball Federation over five seasons (2018–2019 through 2023–2024), analyzing a total 545 teams over three age categories: 178 U14 teams, 183 U16 teams and 184 U18 teams. Games without audience and the 2020–2021 season were not taken into account. Through a two-step cluster analysis, teams were classified according to ability into five groups: Foundational, Development, Competitive, High Performance, and Élite. The team’s ability had significant impact both on HA and HW (p < 0.001). RESULTS: Foundational teams showed significantly lower values of HA (50.0%) and HW (10.0%) when compared to groups of greater ability, whereas Élite teams reached the highest HW values (88.8%). Across categories, significant differences were observed in HA, with values increasing from U14 (50.0%) to U16 (53.9%) and U18 (54.2%), which indicates a small increase consistent with age, whereas no significant differences were found in HW. The team’s ability, rather than the age category, was identified as the major factor impacting HA and HW. Foundational teams showed the lowest HA and HW values; Development teams reached the highest HA, and Élite teams achieved the highest HW. CONCLUSION: These findings indicate that the team’s ability plays a decisive role in the two performance results under study, whereas age category has only a limited influence.